2021
DOI: 10.1016/j.jhazmat.2020.123647
|View full text |Cite
|
Sign up to set email alerts
|

Biochar from pyrolyzed Tibetan Yak dung as a novel additive in ensiling sweet sorghum: An alternate to the hazardous use of Yak dung as a fuel in the home

Abstract: Yak dung is used as fuel in Tibetan homes; however, this use is hazardous to health. An alternative use of the dung that would be profitable and offset the loss as a fuel would be very 2 beneficial. Sweet sorghum silage with yak dung biochar as an additive was compared with a control silage with no additives and three silages with different commercial additives, namely Lactobacillus buchneri, Lactobacillus plantarum and Acremonium cellulase. Biochar-treated silage had a significantly greater concentration of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…They are raised between 3000 and 5000 m above sea level and are well adapted to the harsh conditions of the QTP. Yaks provide meat [ 2 ] and milk [ 3 , 4 ] for food, dung for fuel, and wool for clothes [ 5 ], and they serve as a cultural symbol for Tibetans [ 6 ]. They are also important in maintaining stability of the alpine ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…They are raised between 3000 and 5000 m above sea level and are well adapted to the harsh conditions of the QTP. Yaks provide meat [ 2 ] and milk [ 3 , 4 ] for food, dung for fuel, and wool for clothes [ 5 ], and they serve as a cultural symbol for Tibetans [ 6 ]. They are also important in maintaining stability of the alpine ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…In all, it should be pointed out that in terms of substrate by substrate, the BMP before and after ensiling was not significantly different (P < 0.05), consistent with the results of other authors. 16,47 However, increased TS and ES additive significantly improved the BMP of WH.…”
Section: Resultsmentioning
confidence: 95%
“…Compared to the silages without ES additive, the increase in BMP of co-ensiled silages at TS of 20%, 30% and 40% was 22.05%, 27.94% and 39.70% respectively. Vervaeren et al 46 reported a 22.5% increase in the BMP of maize silage using biological additives while other authors like Gallegos et al 16 and Bai et al 47 have reported that biological additives like lactic acid bacteria had no significant effect on BMP of Elodea and sweet sorghum silages respectively. In the present study, the combined effect of TS (40%) and additive increased the BMP of WH by 63.78%.…”
Section: Resultsmentioning
confidence: 98%
“…Sweet sorghum (Sorghum bicolor Moench) is an important annual forage crop widely distributed all over the world (Bai et al, 2021;Ran et al, 2021;Wang et al, 2021). As a C 4 plant, its high yield, sugar-rich stalks and high resistance to adverse environments make it the best choice for forage production in arid and semi-arid areas where water shortage limits silage corn production (Huang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%